Driver trust in five driver assistance technologies following real-world use in four production vehicles. (29th May 2017) - Kidd, David G.; Cicchino, Jessica B.; Reagan, Ian J.; Kerfoot, Laura B.
ABSTRACT: Objectives : Information about drivers' experiences with driver assistance technologies in real driving conditions is sparse. This study characterized driver interactions with forward collision warning, adaptive cruise control, active lane keeping, side-view assist, and lane departure warning systems following real-world use. Methods : Fifty-four Insurance Institute for Highway Safety employees participated and drove a 2016 Toyota Prius, 2016 Honda Civic, 2017 Audi Q7, or 2016 Infiniti QX60 for up to several weeks. Participants reported mileage and warnings from the technologies in an online daily-use survey. Participants reported their level of agreement with five statements regarding trust in an online post-use survey. Responses were averaged to create a composite measure of trust ranging from −2 (strongly disagree) to +2 (strongly agree) for each technology. Mixed-effect regression models were constructed to compare trust among technologies and separately among the study vehicles. Participants' free-response answers about what they liked least about each system were coded and examined. Results : Participants reported driving 33, 584 miles during 4 months of data collection. At least one forward collision warning was reported in 26% of the 354 daily reports. The proportion of daily reports indicating a forward collision warning was much larger for the Honda (70%) than for the Audi (18%), Infiniti (15%), and Toyota (10%). Trust was highest for side-view assist (0.98) and lowest for active lane keeping (0.20). Trust in side-view assist was significantly higher than trust in active lane keeping and lane departure warning (0.53). Trust in active lane keeping was significantly lower than trust in adaptive cruise control (0.67) and forward collision warning (0.71). Trust in adaptive cruise control was higher for the Audi (0.72) and Toyota (0.75) compared with the Honda (0.30), and significantly higher for the Infiniti (0.93). Trust in Infiniti's side-view assist (0.58) was significantly lower than trust in Audi (1.17) and Honda (1.23) systems. Coding of answers to free-response questions showed that more than 80% of complaints about Honda's adaptive cruise control were about the way it functioned and/or performed. Infiniti's side-view assist was the only one with complaints mentioning circumstances where it was used. Trust in forward collision warning, lane departure warning, and active lane keeping was not significantly different among vehicles. Conclusions : Driver trust varied among driver assistance technologies, and trust in adaptive cruise control and side-view assist differed among vehicles. Trust may affect real-world use of driver assistance technologies and limit the opportunity for the systems to provide their intended benefits.